2021
DOI: 10.3389/fphys.2021.789507
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen, a Novel Therapeutic Molecule, Regulates Oxidative Stress, Inflammation, and Apoptosis

Abstract: Molecular hydrogen (H2) is a colorless and odorless gas. Studies have shown that H2 inhalation has the therapeutic effects in many animal studies and clinical trials, and its application is recommended in the novel coronavirus pneumonia treatment guidelines in China recently. H2 has a relatively small molecular mass, which helps it quickly spread and penetrate cell membranes to exert a wide range of biological effects. It may play a role in the treatment and prevention of a variety of acute and chronic inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 122 publications
(136 reference statements)
0
64
0
Order By: Relevance
“…The antioxidant advantages of H 2 gas include [ 317 , 318 ]: (a) selectively scavenging the deleterious ONOO- and •OH radicals, preserving other important ROS and NIS for normal signaling regulation, (b) stronger reductive activity than other dietetic antioxidants as C or E vitamins, (c) enhanced Nrf2 transcription and SOD, CAT and GPx expression [ 319 ] and (d) reduced NADPH oxidase activity [ 320 ]. In addition to reducing oxidative stress, H 2 increases the expression of antiapoptotic proteins (Bcl-xL and Bcl-2) [ 321 ], which could be helpful to attenuate damage induced by IR.…”
Section: Medical Countermeasuresmentioning
confidence: 99%
“…The antioxidant advantages of H 2 gas include [ 317 , 318 ]: (a) selectively scavenging the deleterious ONOO- and •OH radicals, preserving other important ROS and NIS for normal signaling regulation, (b) stronger reductive activity than other dietetic antioxidants as C or E vitamins, (c) enhanced Nrf2 transcription and SOD, CAT and GPx expression [ 319 ] and (d) reduced NADPH oxidase activity [ 320 ]. In addition to reducing oxidative stress, H 2 increases the expression of antiapoptotic proteins (Bcl-xL and Bcl-2) [ 321 ], which could be helpful to attenuate damage induced by IR.…”
Section: Medical Countermeasuresmentioning
confidence: 99%
“…Generally, hydrogen can be administered in drinking water, 30 bathing water 44 oral or topical medicines, and 28 inhalations or injections of hydrogen saline. 2 This can reduce acute neuronal symptoms, soft tissue injuries or other diseases. Molecular hydrogen only up to 1.6 ppM (0.8mM) can be dissolved in water.…”
Section: Molecular Hydrogen Administrationmentioning
confidence: 99%
“…In future, the sunscreen should have multipurpose uses, besides protecting skin from sunlight, it should heal injuries and take care of wounded tissue, nerves, skin and some other problems. 2 We can design such multipurpose sunscreen by loading bio-friendly photocatalyst in a hydrogel (Figure 5). A person must breathe, bathe, drink, or consume saline as part of the traditional hydrogen administration strategy, but a sportsman cannot afford to do so while playing.…”
Section: Why Do We Need a Special Sunscreen For Athletics?mentioning
confidence: 99%
“…The Chinese National Health and Medical Commission in 2020 recommended the use of inhaled hydrogen in addition to oxygen therapy for anti-cancer, anti-inflammatory and anti-oxidant treatments [ 29 ]. Hydrogen has been suggested as a new complementary therapy against stroke, which, e.g., reduces oxidative stress, neuroinflammation and apoptosis [ 22 , 30 , 31 , 32 ]. Despite many inaccuracies, the selective ability to scavenge free radicals and heal inflammation are still widely accepted mechanisms of the action of hydrogen [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen has been suggested as a new complementary therapy against stroke, which, e.g., reduces oxidative stress, neuroinflammation and apoptosis [ 22 , 30 , 31 , 32 ]. Despite many inaccuracies, the selective ability to scavenge free radicals and heal inflammation are still widely accepted mechanisms of the action of hydrogen [ 32 ]. Clinical trials have shown that hydrogen treatment is safe and effective in patients with asthma and chronic obstructive pulmonary disease [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%